2015
DOI: 10.1021/acs.jpcc.5b09046
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Room Temperature Oxidation on Crystal Structure and Exchange Bias Effect in Co/CoO Nanoparticles

Abstract: We describe here how the exchange bias effect in Co/CoO nanoparticles depends on the size focusing and temperature treatment of precursor Co nanoparticles before oxidation at ambient conditions. By appealing to magnetization, microscopy, neutron, and synchrotron X-ray measurements, we found that as-synthesized Co nanoparticles readily oxidize in air only after 20 days. The highest exchange bias field of 814 Oe is observed at T = 2 K. When the same nanoparticles are centrifuged and annealed at 70 °C under vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Hence, we can conclude that the measured asymmetric hysteresis loops are purely originating from the presence of a DMI-induced tilt of the local magnetization, making these shifted loops a unique and straightforward fingerprint for the existence of the DMI. Moreover, we like to emphasize that the possibility of an oxidation-induced exchange bias effect to explain our data is excluded: it has been experimentally demonstrated that, at the interface between Co/AlOx, over-oxidized Co may lead to an antiferromagnetic CoO and exhibit asymmetric hysteresis loops 49 . Although the shift in hysteresis loop from the exchange bias could occur in our system, it should be irrespective of the in-plane field and the shape of the microstructure, i.e., this would show up as a shifted hysteresis for Hx = 0 and for all geometries including square patterns.…”
mentioning
confidence: 96%
“…Hence, we can conclude that the measured asymmetric hysteresis loops are purely originating from the presence of a DMI-induced tilt of the local magnetization, making these shifted loops a unique and straightforward fingerprint for the existence of the DMI. Moreover, we like to emphasize that the possibility of an oxidation-induced exchange bias effect to explain our data is excluded: it has been experimentally demonstrated that, at the interface between Co/AlOx, over-oxidized Co may lead to an antiferromagnetic CoO and exhibit asymmetric hysteresis loops 49 . Although the shift in hysteresis loop from the exchange bias could occur in our system, it should be irrespective of the in-plane field and the shape of the microstructure, i.e., this would show up as a shifted hysteresis for Hx = 0 and for all geometries including square patterns.…”
mentioning
confidence: 96%
“…It has been shown that it is possible to tune the EB by tuning the core size and shell thickness by controlled synthesis giving more insights into this field. , Moreover, using metal nanoparticles as a seed, various core–shell heterostructures have been reported such as Co/CoO, , Ni/NiO, Mn/Mn 3 O 4 , or metal oxide with different oxidation states such as Mn 3 O 4 /MnO . Systems using different metal oxides such as Fe 3 O 4 /Co, Fe 3 O 4 /FeO, Fe 3 O 4 /CoO, Fe 2 O 3 /CoO, MnO/Mn 3 O 4 , Cr 2 O 3 /CrO 2 , BiFeO 3 /CoFe 2 O 4 , and even Fe/Cr have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that it is possible to tune the EB by tuning the core size and shell thickness by controlled synthesis giving more insights into this field. 21,31 Moreover, using metal nanoparticles as a seed, various core−shell heterostructures have been reported such as Co/CoO, 12,32 Ni/NiO, 33 40 and even Fe/Cr 41 have also been reported. Additionally, transition-metal-based oxides with various core−shell morphologies show tunability in magnetic response also in accordance with their internal structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3,4,7 A majority of the AFM phases are oxides of FM transition metals, and the disordered oxide shell is due to uncontrolled oxidation of the FM core. 8,9 In addition to that, nanocomposites have been designed with randomly distributed counterparts to demonstrate the EB effect. 10−13 However, nanostructures suffer from disordered AFM/FM interfaces which result in a large fraction of uncompensated spins at the interface, thus reducing the EB and hence lowering the induced anisotropy as compared to thin films and multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the NPs demonstrating EB involve systems with a FM core and AFM shell, where T C > T N according to the Meiklejohn and Bean paradigm. ,, A majority of the AFM phases are oxides of FM transition metals, and the disordered oxide shell is due to uncontrolled oxidation of the FM core. , In addition to that, nanocomposites have been designed with randomly distributed counterparts to demonstrate the EB effect. However, nanostructures suffer from disordered AFM/FM interfaces which result in a large fraction of uncompensated spins at the interface, thus reducing the EB and hence lowering the induced anisotropy as compared to thin films and multilayers. , In the past decade, there have been efforts to create inverted core–shell NPs where the AFM core was shelled with FM or FiM materials. ,,− The basic idea was to develop biphasic materials where the EB will show nonmonotonic dependence on the core diameter. These materials also exhibit large H C and spontaneous FM/FiM order.…”
Section: Introductionmentioning
confidence: 99%